ANALISIS KOMUNIKASI PEMASARAN TOKO BUKU SALEMBA TERHADAP NILAI PENCITRAAN PELANGGAN DENGAN APLIKASI SOFTWARE SPSS - Akmaludin, Akmaludin (www.bsi.ac.id, 2013)
With the large number of people and the advancement of education, a lot of people that require the development of knowledge that comes from reading materials such as books, novels, magazines, and other reading materials. One provider of reading material is a book store. Judging from the level of competition bookstore today's highly competitive, because it's allmarketing efforts for the development of urgently needed. It can be seen from the many new bookstore standing or that has been growing rapidly, when viewed from one aspect of education is certainly a lot of need for reading. By considering these aspects then Salemba bookstore trying to develop its marketing efforts in the field of libraries with all age groups and gender. Throughpromotional efforts and pemasaranya Salemba bookstore doing a lot of promotion and marketing strategies that have a program of work are like the advertising and marketing strategy with the use of a membership card ownership. One strategy to do is to increase brand awareness to promoteBookstore to its customers and create a unique selling proposition strategy orientation by binding to its customers through the card to the customer to prioritize breakthrough image enhancement bookstore. Through this marketing strategy, then Salemba bookstore trying to gauge the level of customer imaging to bookstores and also find a way to change its marketing strategy in the futurethrough serjumlah respondents to rate the effectiveness of marketing communications by using SPSS application. With the analysis results obtained will serve as a decision making for progress in the future.